Hibriditas Budaya Dalam Pesantren Gontor - Lutfi Nurfadli (FKIP UNSULTRA, 2025)
This study aims to examine the forms of modernity implemented at Gontor, as well as how Pondok Modern Darussalam Gontor integrates traditional pesantren values with elements of modernity in its educational and organizational systems. Employing a qualitative approach and the concept of cultural hybridity developed by Homi K. Bhabha, the study finds that Gontor has successfully established an educational model that structurally combines Islamic religious sciences with general knowledge in a unified curriculum. Furthermore, it adopts a professionally organized management system. Gontor does not solely focus on Islamic teachings but also incorporates foreign language instruction, general sciences, and leadership training, positioning itself as an adaptive educational institution in the face of global challenges. Despite the integration of modern elements, Gontor consistently upholds traditional pesantren values such as sincerity (ikhlas), simplicity (sederhana), self-reliance (mandiri), Islamic brotherhood (ukhuwah Islamiyah), and freedom (hurriyah). These values remain central within the institution. The findings of this research suggest that Gontor's cultural transformation presents a viable model for other pesantren in navigating globalization while preserving Islamic identity. This study contributes to a deeper understanding of the application of modernity in Islamic boarding school education and highlights the significance of integrating traditional values with modern elements to develop a more relevant and responsive Islamic educational system in the contemporary era